TENDENCIAS DEL NIVEL DEL MAR EN LAS COSTAS DEL CARIBE MEXICANO - Ruiz-Ramírez, Jennifer D.; Euán-Ávila, Jorge I.; Torres-Irineo, Edgar (European Scientific Journal, ESJ, 2014)
Sea level trends from four stations of Quintana Roo, Mexican Caribbean are presented. Time series data were obtained from the Red Mareográfica Institucional of the Secretaría of Marina, Mexico Navy and from the Servicio Mareográfico Nacional of the Universidad Nacional Autónoma of México; further regional time series data were collected jointly from the TOPEX / Poseidon, Jason-1 and OSTM/Jason-2 altimeters on the Caribbean Sea over a period of 20 years. For each gage, daily data were used and analyzed by setting the trend line. The trend for each station is positive: Isla Cozumel with 0.3 mm yr-1, Isla Mujeres with 3.6 mm yr-1, Mahahual with 1.2 mm yr-1 and Puerto Morelos with 1.4 mm yr-1. The overall trend for the gauges is positive, with 1.6 mm yr-1, less than the trend depicted by the altimeters on the Caribbean region (2.0 mm yr-1). We concluded that locally, the increase is not homogeneous and regional trends variations are not only positive, in certain periods are negative, this was yielded with longer time scales, as observed with radars. This coincides with the results from the IPCC which show that these increases are not similar throughout the world and it is a priority to know the change rates and individual factors affecting in each region, in order to effectively address the risks associated with sea level rising.